PERLINDUNGAN KONSUMEN ATAS PENJAMINAN MUTU MAKANAN LONTONG PLASTIK YANG BEREDAR DI PASARAN DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DI KECAMATAN TAMPAN - Andriani, Dedek Suci; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One of the products of technological sophistication is plastic packaging,packaging often used by business actors to pack food. The advantages of plasticpackaging itself is impressed practical, simple, and clean. However, the actual plasticpackaging can endanger health if used in hot temperatures is to pack lontong whoparticipated in the manufacturing process (boiling / steaming). This is very consumerhealth and has violated Article 4 Letter (a) Law Number 8 Year 1999 on ConsumerProtection namely: Right to comfort, safety, and safety in consuming goods andservices. The purpose of writing this thesis, namely: First, consumer protectionplastic food lontong in Kecamatan Tampan. Secondly, the responsibility of businessactors selling plastic lontong food based on Law Number 8 of 1999 on ConsumerProtection.This type of research can be classified in the type of sociological research,because in this study the authors directly conduct research spaciousness. Researchlocation and population along with samples in this writing is on Consumer, andLontong Plastic Food Seller in Kecamatan Tampan Pekanbaru City. The data sourcesconsist of primary data and secondary data, data collecting technique throughinterview and distributing questionnaires to consumers as respondents andDiscussion to Central Supervisor of Drugs and Food as practitioners in the field.From the results of research problems there are two main things that can beconcluded. First, the Consumer Protection of plastic lontong food in KecamatanTampan, that consumers are not aware of any harm or impact of consuming plasticlontong food, with the fact that consumers' knowledge of their rights protected by lawis still lacking. Second, the responsibility of the seller of lontong food seller businesspursuant to Law Number 8 Year 1999 concerning Consumer Protection for damage,pollution, or consumer loss due to consuming goods and services. Suggestion,consumers are expected to be more independent and can protect themselves from theexistence of things that can harm consumers. Better business people selling lontongfood better cook lontong by using banana leaves or ketupat. Besides, it is expectedthat the development and training of consumers and supervision of the SupervisoryAgency for Drugs and Food on consumers of business actors who have harmed theconsumers.Keywords: Consumer Protection, Plastic Lontong Food